Linee interpretative sull'ispirazione schopenhaueriana di Piero Martinetti e di Teodorico Moretti-Costanzi - Bozza, Martino (Nuovo giornale di filosofia della religione, 2019)
The work and thought of Arthur Schopenhauer have inspired many of those who have devoted themselves to philosophical research. For the Italian panorama of the twentieth century, it is striking to find two very different authors, such as Teodorico Moretti-Costanzi and Piero Martinetti, who both found Schopenhauer as a master of thought. The two Italian philosophers, while maintaining a sidereal distance for their personal path of thought, can be caught in an unequivocal effort to deepen the dimension of the religious in philosophy and appear absolutely original as, in this common purpose, both find in Schopenhauer an inescapable reference . The German philosopher in fact represents better than other authoritative references the one who in concentrating in the dimension of the factual human reality has been able to grasp how this cannot be considered exhausted in itself but, on the contrary instead, lives all in the reference to an transcendence not determinable and not knowable . From this assumption the paths of thought start, which are then articulated in an absolutely different way, by Teodorico Moretti-Costanzi and Piero Martinetti. And with Schopenhauer, therefore, the two Italian philosophers must confront each other. For Moretti- Costanzi the comparison represents a way to validate his own reading of reality and to place Schopenhauer in an asceticism that certainly can represent a reading at least original of the German philosopher if not even forced. Martinetti focuses on a more analytical and linear consideration of Schopenhauerian thought, capturing in it all the contents that must be put in place to do philosophy in a high, pure way. Thus Schopenhauer becomes a common guide for doing philosophy for these two Italian philosophers of the twentieth century, so distant in the way of walking and perhaps so close in wanting to trace a path of philosophy that aims high.